The Design of Poly(lactide-co-glycolide) Nanocarriers for Medical Applications - Essa, Divesha; Kondiah, Pierre P. D.; Choonara, Yahya E.; Pillay, Viness (Frontiers in Bioengineering and Biotechnology, 2020)
Polymeric biomaterials have found widespread applications in nanomedicine, and PLGA in particular has been successfully implemented in numerous drug delivery formulations due to its synthetic malleability and biocompatibility. However, the need for preconception in these formulations is increasing, and this can be achieved by selection and elimination of design variables in order for these systems to be tailored for their specific applications. The starting materials and preparation methods have been shown to influence various parameters of PLGA-based nanocarriers and their implementation in drug delivery systems, while the implementation of computational simulations as a component of formulation studies can provide valuable information on their characteristics. This review provides a critical summary of the synthesis and applications of PLGA-based systems in bio-medicine and outlines experimental and computational design considerations of these systems.